ORGANISATIONAL AND INDIVIDUAL FACTORS AS CORRELATES OFWORKERS’ JOB INVOLVEMENT IN CIVIL SERVICE ESTABLISHMENTS IN OYO STATE, NIGERIA (2016)
Low Job Involvement (JI) of civil servants has impacted negatively on individual and organisational goal achievement in the civil service. Low JI has brought about low productivity which eventually affects the rates of economic growth and development. Previous studies have largely focused on JI in the private enterprise with associated personal variables with little attention on combined organisational and individual factors. This study, therefore, examined the extent to which organisational factors (Training Opportunities (TO), Leadership Style (LS), Communication System (CS), Environmental Variability (EV), Gender Policy (GP) and individual factors (sex, Educational Attainment (EA), Emotional Intelligence (EI), Social Interaction (SI), Workers Perception (WP) and Career Orientation (CO) correlate with JI (Team Spirit (TS), Sense of Responsibility (SR), Prompt and Regular Office Attendance (PROA), Enthusiasm on the Job (EJ), Work Inclusion (WI) and Internal Motivation (IM) in civil service establishments in Oyo State, Nigeria. The study was anchored on Vroom’s theory and descriptive survey design was adopted. Purposive sampling technique was used to select six each of state and federal core service-oriented civil service establishments (Ministries of Information, Lands, Works, Health, Environment and Agric) because of their acceptability to study their establishment. Stratified random sampling technique was used in selecting 812 civil servants across the 12 selected establishments. Training opportunities (r=0.81), LS (r=0.78), CS (r=0.84), EV (r=0.85), GP (r=0.76), EI (r=0.89), SI (r=0.75), WP (r=0.87), CO (r=0.77) and Workers’ Job Involvement (r=0.80) scales were used for data collection. These were complemented with 12 In-depth Interview sessions with one civil servant from each establishment. Descriptive statistics, Pearson product moment correlation, t-test and Multiple regression were used to analyse quantitative data at 0.05 level of significance while qualitative data were content analysed. All the components of JI were observed to be low: prompt and regular office attendance (27.1%), team spirit (30.0%), work inclusion (34.5%), job enthusiasm (35.5%), sense of responsibility (39.4%) and internal motivation (39.4%). Organisational and individual factors had joint significant correlation (R=0.80) with JI in the civil service establishments (F(10,800)=723.42); accounting for 63.7% of its variance. Gender policy (β=0.44), career orientation (β=0.36), sex (β=0.22), social interaction (β=0.19), environmental variability (β=0.17), educational attainment (β=0.15), emotional intelligence (β=-0.12), training opportunities (β=0.11) and communication system (β=0.10) had significant relative contributions with JI. There was no significant difference in the level of JI between civil servants in the federal and state establishments. The perceived poor job specification in the civil service system, role ambiguity and conflict make workers to discharge their duties with complacency and negative attitude. Formulation and implementation of gender policy, positive career orientation, improved social interaction, high emotional intelligence and training opportunities influenced workers’ job involvement in civil service establishments in Oyo State, Nigeria. Civil service system in Nigeria should be restructured taking into consideration these factors so as to sustain high job involvement among civil servants.